The effects of human resource practices on firm growth - Ilias P. Vlachos (International Journal of Business Science & Applied Management (IJBSAM), 2009)
Although the connection between firm growth and labour is well documented in economics literature, only recently the link between human resources (HR) and firm growth has attracted the interest of researchers. This study aims to assess the extent, if any, to which, specific HR practices may contribute to firm growth. We review a rich literature on the links between firm performance and the following HR practices: (1) job security (2) selective hiring, (3) self-managed teams (4) compensation policy, (5) extensive training, and (6) information sharing. We surveyed HR managers and recorded their perceptions about the links between HR practices and firm growth. Results demonstrated that compensation policy was the strongest predictor of sales growth. Results provide overall support for all HR practices except of job security. Eventually, selecting, training, and rewarding employees as well as giving them the power to decide for the benefit of their firm, contribute significantly to firm growth.
Keywords: 650; human resource practices; firm growth; selective hiring; compensation policy